2015
DOI: 10.1074/jbc.m114.610196
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Plant Homeodomain Finger 6 (PHF6) Recognition by the Retinoblastoma Binding Protein 4 (RBBP4) Component of the Nucleosome Remodeling and Deacetylase (NuRD) Complex

Abstract: Background:The PHF6 gene is mutated in patients with Börjeson-Forssman-Lehmann syndrome, T-cell acute lymphoblastic leukemia, and acute myeloid leukemia. The PHF6 protein is a newly identified interactor with the NuRD complex. Results: The complex structure of the NoLS region of PHF6 bound to RBBP4 was solved. Conclusion: By interacting with the RBBP4 component, PHF6 associates with the NuRD complex. Significance: Association with the NuRD complex implicates a role for PHF6 in chromatin structure modulation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 37 publications
(47 reference statements)
1
27
0
Order By: Relevance
“…These proteins share a common N‐terminal RBBP‐binding motif . Other regulators such as Zic2 , PHF6 ZMYND8 and the lysine demethylase LSD1 have also been shown to associate with NuRD. In some cases, these proteins most likely represent bridges between NuRD and specific genomic sites, whereas in other cases they might expand the functional diversity of the complex by creating distinct NuRD assemblies in different biological contexts.…”
Section: Resultsmentioning
confidence: 99%
“…These proteins share a common N‐terminal RBBP‐binding motif . Other regulators such as Zic2 , PHF6 ZMYND8 and the lysine demethylase LSD1 have also been shown to associate with NuRD. In some cases, these proteins most likely represent bridges between NuRD and specific genomic sites, whereas in other cases they might expand the functional diversity of the complex by creating distinct NuRD assemblies in different biological contexts.…”
Section: Resultsmentioning
confidence: 99%
“…al. 15 ), FOG-1 (1-15; MSRRKQSNPRQIKRS) 14 , PHF6 (157-171; KSKKKSRKGRPRKTN) 13 and H4 (16-41; KRHRKVLRDNIQGITKPAIRRLARRG) 17 (Fig. 1A and 1B).…”
Section: Developing a Suite Of Assays For High Throughput Screeningmentioning
confidence: 98%
“…From the NuRD complex, PHF6 was shown to co-purify with CHD3, CHD4, RBBP4, RBBP7 and HDAC1, wherein, PHF6 interaction with RBBP4 and CHD4 was restricted to the nucleoplasm, despite its presence in the nucleolus as well 53 . Among the various co-purified components of the NuRD complex, a direct interaction has been reported between RBBP4 and PHF6 and the interaction has been characterized both structurally and biophysically 13,54 . A structure of full-length RBBP4 in complex with a PHF6 peptide (157-171 amino acids) showed that a negatively charged surface at the top of the RBBP4 β-propeller is essential for binding to a PHF6 peptide (a dissociation constant of 7.1 ± 0.4 µM; Table 1) 13 .…”
Section: Phf6mentioning
confidence: 99%
See 2 more Smart Citations